Colchicine Myopathy: A Case Series Including Muscle MRI and ABCB1 Polymorphism Data - Gupta, Mehul; Nikolic, Ana; Ng, Denise; Martens, Kristina; Ebadi, Hamid; Chhibber, Sameer; Pfeffer, Gerald (Frontiers in Neurology, 2019)
Colchicine is a medication most commonly used in the treatment of gout and familial mediterannean fever. A rare complication of therapy is toxicity causing proximal myopathy and polyneuropathy. Colchicine myopathy has been associated with the coadministration of other medications with colchicine, such as statins or tacrolimus, and is more common in patients with renal impairment. Otherwise, it is unclear which patients are at greatest risk of developing this adverse drug reaction. ABCB1 is important to the metabolism of colchicine, so we speculated that it was possible that colchicine myopathy patients may have a particular genotype that is associated with this side effect. We describe two cases of colchicine myopathy which occurred with co-administration of rosuvastatin. From one case, we present the first published data on muscle MRI in this condition. We additionally present an analysis of four genetic polymorphisms in ABCB1 and transcript levels in muscle tissue, and demonstrate the descriptive finding of reduced ABCB1 transcript levels in the colchicine myopathy patients.